Covid-19 vaccine acceptance and hesitancy among medical students of Faisalabad - Mohi Ud Din; Umer Shahid; Abdul Qudoos; Roman Ahmed; Muazzama Sohail; Saima Javed (Journal of Rawalpindi Medical College)
Objectives: The study was conducted to determine the Covid-19 vaccine acceptance and hesitancy among the medical students who are more susceptible to be infected being the frontline workers.